Dynamic slicing of distributed programs - Korel, Bogdan; Ferguson, Roger (Zielona Góra: Uniwersytet Zielonogórski)
A static slice "S" of a sequential program "Q" is an executable part of "Q" that computes the same function as "Q" does in a subset of variables at some selected point of interest. As originally introduced, it involves all potential terminating program executions. In debugging, however, we typically deal with a particular incorrect execution and are interested in locating the cause of incorrectness of that execution. Therefore, we are interested in a slice, referred to as a dynamic slice, that preserves the program's behavior for a specific input.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka